2015
DOI: 10.1007/s10902-015-9701-1
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and Adolescents’ Conceptions of Happiness

Abstract: Previous research on children's and adolescents' happiness has mainly focused on the different variables that may contribute to it. However, very few studies have investigated the beliefs that children and adolescents hold about happiness. It is important to study developmental differences in the conceptions of happiness as beliefs affect people's emotions and behaviors, and they may help explain how children and adolescents strive for their own (and potentially others') happiness. To that aim, we asked 162 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 64 publications
3
24
1
2
Order By: Relevance
“…A study with Brazilian 5 to 12 year olds showed age differences in what youth think happiness is, where younger children more often mention leisure activities but older children mention how happiness feels (Giacomoni, de Souza, & Hutz, 2014). Similar shifts in conceptions of happiness were found across a sample of Spanish 9 to 16 year olds, where children more often mentioned hedonic factors (i.e., good feelings) but adolescents more often mentioned broader eudaimonic factors, such as harmony and purpose (Lópéz-Perez, Sánchez, & Gummerum, 2016). Additionally, another study with Porteguese adolescents indicated they report that happiness involves both hedonic and eudaimonic components (Freire, Zenhas, Tavares, & Iglésias, 2013).…”
Section: Emotional Beliefs and Values In Youthsupporting
confidence: 60%
“…A study with Brazilian 5 to 12 year olds showed age differences in what youth think happiness is, where younger children more often mention leisure activities but older children mention how happiness feels (Giacomoni, de Souza, & Hutz, 2014). Similar shifts in conceptions of happiness were found across a sample of Spanish 9 to 16 year olds, where children more often mentioned hedonic factors (i.e., good feelings) but adolescents more often mentioned broader eudaimonic factors, such as harmony and purpose (Lópéz-Perez, Sánchez, & Gummerum, 2016). Additionally, another study with Porteguese adolescents indicated they report that happiness involves both hedonic and eudaimonic components (Freire, Zenhas, Tavares, & Iglésias, 2013).…”
Section: Emotional Beliefs and Values In Youthsupporting
confidence: 60%
“…An explanation of this age barrier lies within developmental psychology. Children under the age of 12 are considered to be at the concrete operational stage, with reasoning limited to concrete examples rather than abstract or hypothetical concepts (López-Pérez, Sánchez, & Gummerum, 2016). Beyond this age, in adolescence, they enter the formal operational stage (Piaget, 1952) and can reason about abstract concepts without needing concrete examples.…”
Section: Measuring Swb In Childrenmentioning
confidence: 99%
“…Esto es coherente con la serie de investigaciones que se han venido desarrollando en los últimos años (Bojanowska & Zalewska, 2015;Caunt et al, 2013;Denegri et al, 2015;Henderson, Knight, & Richardson, 2013;Huta & Ryan, 2009;López-Pérez et al, 2015;McMahan & Renken 2011;Torner, 2011;Waterman, 1993), y abre la interrogante que muchas de estas investigaciones se han planteado a saber: ¿el predominio en las personas de una concepción más eudaimónica o más hedónica de la felicidad tiene …”
Section: Discussionunclassified
“…Así mismo, el término felicidad ha sido más utilizado generalmente desde la perspectiva hedónica (Diener, Oishi, & Lucas, 2009;Ryan & Deci, 2001) para referenciar una experiencia subjetiva-afectiva predominantemente positiva o placentera. En cambio, se hará un uso más generalizado y se podrá observar que el término felicidad puede ser abordado desde diferentes perspectivas (Caunt et al, 2013;López-Pérez, Sánchez, & Gummerum, 2015).…”
Section: Introductionunclassified